2003
DOI: 10.1113/eph8802490
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Isoprenaline Infusion on Renal Renin and Angiotensinogen Gene Expression in the Anaesthetised Rat

Abstract: In this study, we investigated the ability of acute infusions of isoprenaline to alter renin and angiotensinogen gene expression in the kidney of rats anaesthetised with chloralose‐urethane. Groups of rats received I.V. infusions of either saline or the β‐adrenoceptor agonist isoprenaline at 400 ng kg−1 min−1 for 4 h. The isoprenaline infusion caused a sustained decrease in mean blood pressure of approximately 20 mmHg (P < 0.01), an increase in heart rate of 50 beats min−1 (P < 0.01) and reductions in urine fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 23 publications
(32 reference statements)
0
16
1
Order By: Relevance
“…It has been reported that isoprenaline directly activates β-adrenoceptor on JG cells and stimulates adenylate cyclase to produce cAMP, which causes a cAMP-dependent protein kinase-A activation resulting in renin release [20]. In the present study, isoprenaline was found to increase the PRA by 3-fold in CD38 −/− mice, which was much higher compared to that observed in CD38 +/+ mice.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…It has been reported that isoprenaline directly activates β-adrenoceptor on JG cells and stimulates adenylate cyclase to produce cAMP, which causes a cAMP-dependent protein kinase-A activation resulting in renin release [20]. In the present study, isoprenaline was found to increase the PRA by 3-fold in CD38 −/− mice, which was much higher compared to that observed in CD38 +/+ mice.…”
Section: Discussioncontrasting
confidence: 51%
“…The surgery was performed as described previously [2021]. In brief, after being fasted overnight the mice were anesthetized with ketamine (50 μg/g intraperioneally; Parke-Davis GmbH, Berlin, Germany) and inactin (100 μg/g intraperitoneally; Res Biochemical, Inc., Natick, MA) and then placed on a heated table for maintenance of body temperature at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…JG cells contain ␤ 1 -adrenergic receptors (81,161). The systemic application of the ␤-adrenoreceptor agonist isoproterenol by chronic infusion into rats, both time and dose dependently, stimulates the synthesis and secretion of renin (355,598,802). In addition, isoproterenol infusion increased renin mRNA expression and PRA in rats during normal and high salt intake, but not during low salt intake (355).…”
Section: ␤-Adrenergic Pathwaymentioning
confidence: 99%
“…A histopathological change in PUL is a typical lentigo simplex that shows an increase in nevoid melanocytes in the basal layer of the epidermis. In a rare occasion, PUL has been reported to show a histological finding of ‘lentigo’ with a small cluster of a nevomelanocytic nest in the basal layer [7]. In the present case, histopathology of the biopsy specimen revealed a typical compound-type nevus.…”
Section: Discussionmentioning
confidence: 63%